Uso De Frecuencias Sonoras En La Inhibición Del Crecimiento De Enterobacterias (2024)
Dr. Royal Raymond Rife, a 20th century scientist, developed a microscope and proposed the use of sound waves at different frequencies to eliminate pathogenic microorganisms, which he called Deadly Oscillatory Frequency (MOR). His research is the basis for an analysis of the response of various enterobacteria to different Hertz (Hz) frequencies, emphasizing the Escherichia coli bacteria, and the growing resistance to antibiotics.